Loxapine in the Treatment of Manic and Psychotic Symptoms in an Individual Intolerant to Multiple Mood-Stabilizing and Antipsychotic Medications - Im, David S.; Capitanov, Marina; VandenBerg, Amy M. (Case Reports in Psychiatry, 2023)
First-line treatments for schizophrenia and schizoaffective disorder include antipsychotics and mood stabilizers, but their use may at times be limited due to severe adverse events. This case describes a 41-year-old male with a history of schizoaffective disorder and polysubstance use who was admitted to an inpatient psychiatry unit for acute manic and psychotic symptoms in the setting of absconding from his residential home and noncompliance with prescribed psychiatric medications. During his inpatient psychiatric hospitalization, he experienced DRESS (drug reaction with eosinophilia and systemic symptoms) with valproate, nephrogenic diabetes insipidus with lithium, potential neuroleptic malignant syndrome with risperidone, and orthostasis/tachycardia with clozapine. He ultimately achieved stabilization of manic and psychotic symptoms with loxapine without experiencing adverse events. This report highlights the potential utility of loxapine in individuals with schizoaffective disorder intolerant to standard mood-stabilizing and antipsychotic medications.